REFLEKSI TEOLOGIS DIETRICH BONHOEFFER MELAWAN SEPAK TERJANG NAZI-HITLER - Y.B. Prasetyantha (Jurnal Orientasi Baru, 2017)
"Silence in the face of evil is itself evil: God will not hold us guiltless. Not to speak is to speak. Not to act is to act." Though not found in his works, the phrase has often been attributed to Dietrich Bonhoeffer. Who is Bonhoeffer and why is that phrase so attached to him? Using a historical critical method and text analysis, this article is to present Bonhoeffer's story of discipleship and his theological reflection in his struggle against the Nazi during the Second World War. For Bonhoeffer, Hitler is anti-Christ. Therefore, for him, faith means a struggle and theology must be politically characterized. In Christ, God being human, Christians live their faith concretely in the reality of the world.